Isolation of Lactic Acid Bacteria from California Papaya and Antibacterial Activity as a Potential Starter Culture - Harmoko, Deni; Suryani, Elsa Mega; Ningrum, Rizka Kusuma (Jurnal Biologi Tropis, 2025)
Papaya fruit has many benefits for body health. Lactic acid bacteria can be used as a starter culture to produce more diverse foods (food diversification) and increase product shelf life. This study was conducted to obtain LAB isolates from California papaya that have potential as starter cultures. The methods in this study include the LAB isolation stage followed by the gram staining process, endospore staining, catalase test, hemolytic test, and antibacterial activity test using S. aurius and E. coli as indicator bacteria. Data were analyzed statistically using one-way ANOVA and Tukey’s post hoc test at 5% of significance level. The total count (TPC) of LAB in California papaya samples was 3.6x105 CFU/mL. The results of LAB isolation from California papaya obtained 14 LAB isolates, after going through the testing and screening stages obtained 8 LAB isolates that could potentially be used as starter culture candidates, namely isolates DPC1, DPC5, DPC6, DPC7, DPC10, DPC11, DPC12, DPC14. Isolate DPC6 is an isolate with the highest antibacterial activity in inhibiting the growth of S. aureus and E. coli bacteria, so it is a potential bacterial candidate that can be used as a starter culture.